Effect of the Antenatal Care Group Model on Childbirth Preparedness among Pregnant Women: A Quasi-Experimental Study - Budiarti, Kurniawan Dewi; Sulliyawati, Eti; Sulastin, Sulastin; Badriyah, Suci (Chakra Brahmanda Lentera Institute, 2025)
Background: Childbirth preparedness is essential to prevent complications and improve the safety of both mothers and infants. Knowledge, attitudes, and social support strongly influence maternal readiness. Group antenatal care (ANC) has been shown to enhance maternal engagement, but most studies have focused on face-to-face services. However, limited studies have examined digital ANC groups in Indonesian primary care settings. Therefore, this study aimed to analyze the effect of WhatsApp-based group ANC on maternal readiness for childbirth.. Methods: This study employed a quasi-experimental pre–post design with a control group, following the TREND reporting guideline. A total of 40 pregnant women in their second or third trimester were purposively selected. Inclusion criteria were residence in Samarang, no medical complications, and willingness to participate; exclusion criteria included refusal or diagnosed complications. The instrument was a validated childbirth preparedness questionnaire (15 items, Cronbach’s alpha = 0.87). The intervention was delivered via a WhatsApp group over two weeks (six sessions), facilitated by trained midwives using validated materials. Data were analyzed using independent t-tests after testing normality and homogeneity, with a significance level of 0.05, 95% confidence interval (CI), and effect size calculated using Cohen’s d. Results: The mean preparedness score was higher in the experimental group (58.80 ± 5.01) compared to the control group (54.35 ± 6.43). The mean difference of 4.45 points was statistically significant (p < 0.001; 95% CI [2.1–6.7]) with a moderate-to-large effect size (Cohen’s d = 0.78). These findings indicate that WhatsApp-based ANC groups significantly improved maternal knowledge and childbirth preparedness.. Conclusion: WhatsApp-based group ANC effectively enhances maternal childbirth preparedness and is feasible for implementation as a maternal health education strategy in primary care settings.